Tahfidzul Qur'an Learning Innovation Takhassus Tahfidz Class Based on Personalized Mentorship Program - Muslim Mubarok; Ismail; Muhammad Khumaidi Ali (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2025)
This study aims to develop an innovative learning approach for the tahfidzul Qur’an takhassus tahfidz class through a personalized mentorship program. Employing a descriptive qualitative methodology, data were collected from official sources such as books, interviews, and observations. The research was conducted at SMPIT and SMAIT Ar-Rahmah Makassar, utilizing purposive sampling to select informants relevant to the study’s objectives. Data were analyzed using the Miles and Huberman interactive model to gain an in-depth and contextual understanding of the comparison between conventional tahfidzul Qur’an takhassus tahfidz classes and the personalized mentorship-based learning innovation. The findings reveal that the implementation of the personalized mentorship program—including khatam, mutqin, and murajaah components—significantly improves students’ memorization abilities. The program fosters positive changes in daily memorization target achievement and contributes to a more holistic and conducive learning environment. This study highlights the importance of a structured and personalized tahfidz model that enhances memorization effectiveness while addressing individual student needs through continuous evaluation, emotional support, and adaptive mentoring strategies. The proposed approach offers a valuable framework for other Islamic educational institutions seeking to enhance their tahfidz learning systems.